Vincetoxicum emeiense (Asclepiadeae, Asclepiadoideae, Apocynaceae), a new species from Sichuan, China - Zeng, Si-Yuan; Yang, Qiyi; Yu, Jie; Shen, Jian-Yong (Phytotaxa, 2021)
Vincetoxicum emeiense (Apocynaceae), a new species from Emeishan City, Sichuan Province, China, is described and illustrated. It is morphologically similar to V. hui and V. koi but can be distinguished by the glabrous stem, marginally finely ciliate with adaxially puberulent leaves and orange to purple corolla. Color photographs, conservation assessment and other relevant notes are also provided.